Peningkatan Penguasaan Perkalian Melalui Metode Jarimatika Pada Pembelajaran Matematika - Lejiu, Yomanius; Putrini R Harahap, Saima (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2024)
In mathematics learning, students' understanding of the concept of multiplication still has not reached the expected level. Many of them find it difficult and do not like to learn multiplication, which results in low learning achievement. Improving mathematics learning outcomes for class III students at SDN 004 Sangkulirang in multiplication material using the Jarimatika method is the aim of this research. The research was conducted on 26 class III students at SDN 004 Sangkulirang, Sangkulirang District, East Kutai Regency, in the 2023/2024 academic year. The method used in this research is Classroom Action Research (PTK) which consists of two cycles with four stages of implementation. Research data was collected through student observations and learning outcomes tests, then analyzed using descriptive techniques. The research results showed that there was an increase in student learning outcomes after applying the Jarimatika method. In cycle 1, as many as 17 students or 65.38% succeeded in reaching the KKM 68 with an average score of 71. In cycle 2, the number of students who achieved the KKM increased to 24 or 92.30%, with an average score of 82.14. Based on these data, it can be concluded that the application of the Jarimatics method in learning multiplication has succeeded in improving student learning outcomes in mathematics subjects